2002
DOI: 10.1046/j.1475-1313.2002.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of refractive amblyopia by optical correction alone

Abstract: Amblyopia--the commonest vision abnormality of childhood--is characterized by a loss of visual acuity usually of one eye only. Treatment aims to promote function of the amblyopic eye and does this by restricting, usually through occlusion, the competitive advantage of the fellow eye. Recent experimental evidence demonstrates that the recovery of vision following early deprivation is facilitated by increasing visually evoked activity. An analogous approach in humans is to minimise image blur by correcting refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 11 publications
4
74
1
2
Order By: Relevance
“…All children with significant refractive error were instructed to wear spectacles full-time and were scheduled to return for four vision assessments at 6-week intervals from week 0 (onset of spectacle wear) until 18 weeks of refractive adaptation was completed-a period that our previous research indicated would allow for all significant improvement attributable to spectacle wear to have occurred. 14 Children remaining eligible for occlusion (see below for inclusion criteria) entered the occlusion phase and were prescribed 6 hours occlusion per day (a dose considered moderate, allowing for underand over-concordance). Occlusion episodes received were recorded to the nearest minute by an occlusion dose monitor.…”
Section: -12mentioning
confidence: 99%
“…All children with significant refractive error were instructed to wear spectacles full-time and were scheduled to return for four vision assessments at 6-week intervals from week 0 (onset of spectacle wear) until 18 weeks of refractive adaptation was completed-a period that our previous research indicated would allow for all significant improvement attributable to spectacle wear to have occurred. 14 Children remaining eligible for occlusion (see below for inclusion criteria) entered the occlusion phase and were prescribed 6 hours occlusion per day (a dose considered moderate, allowing for underand over-concordance). Occlusion episodes received were recorded to the nearest minute by an occlusion dose monitor.…”
Section: -12mentioning
confidence: 99%
“…Before study entry, all patients had a full ophthalmic assessment including cycloplegic retinoscopy and fundoscopy, and a full orthoptic examination. Inclusion criteria were: age>7 years and amblyopia (strabismic, anisometropic or combined), and acuity difference between the eyes of at least 0.2 logMAR (logarithm of the minimum angle of resolution) for single and crowded optotypes after refractive adaptation [15,20,21]. While most patients received their glasses several months before entering the study, two received their first glasses 8 and 6.5 weeks respectively before baseline acuity was assessed, and in one patient there was a change of the astigmatic component of 0.75 D 7 weeks before.…”
Section: Patient Inclusionmentioning
confidence: 99%
“…Those studies that show a progressive improvement in acuity for up to 18 weeks in some patients after refractive correction alone in anisometropic amblyopia patients use the term ''refractive adaptation period'' [22,23]. In the present study, we did not wait for the refractive adaptation period because, as the duration of treatment increases, treatment compliance decreases.…”
Section: Discussionmentioning
confidence: 93%